1974
DOI: 10.1044/jshr.1703.510
|View full text |Cite
|
Sign up to set email alerts
|

Nonspeech Noun Usage Training with Severely and Profoundly Retarded Children

Abstract: A nonspeech symbol system, consisting of small pieces of masonite cut into various shapes, was used to investigate the learning of noun usage by nonverbal, severely and profoundly retarded children. Results indicated that most such subjects can learn appropriate skills and do so in a short period of time when this nonspeech response mode is employed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1977
1977
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Early investigations, employing manual signs and visual-graphic symbols, focused on demonstrating the feasibility of employing AAC with children and adults with developmental disabilities [e.g., Carrier, 1974;Deich and Hodges, 1977;Romski et al, 1984]. In general, these investigations found that when children and adults were provided with AAC systems, they learned to communicate expressively using the skills they explicitly had been taught.…”
Section: Advances In Aac Researchmentioning
confidence: 99%
“…Early investigations, employing manual signs and visual-graphic symbols, focused on demonstrating the feasibility of employing AAC with children and adults with developmental disabilities [e.g., Carrier, 1974;Deich and Hodges, 1977;Romski et al, 1984]. In general, these investigations found that when children and adults were provided with AAC systems, they learned to communicate expressively using the skills they explicitly had been taught.…”
Section: Advances In Aac Researchmentioning
confidence: 99%
“…One of the higher-functioning boys (eventually among the eight fastest signers) refused to work on the NON-SLIP tasks after a 2-month period. Carrier's descriptions (Carrier, 1974;Carrier & Peak, 1975) of his population were somewhat vague, with general ratings of severe to profound retardation (Adaptive Behavior Scale ratings of 4 and 5 [Heber, 1961]). Comparing the number of children who passed CMP in the present study and in the normative study (107 of 108 in the NON-SLIP normative sample and 2 of 13 in the present sample) reveals a significant difference (Yates corrected Chi Square [81.84] significant beyond .001 level, Siegel, 1956).…”
Section: Discussionmentioning
confidence: 99%
“…A 3-month period seemed an adequate time: Hodges and Deich (1979a) and Deich and Hodges (1982) had reported successful sentence training for severely retarded children within a 3-month period and some learning for profoundly retarded children within a 6-month period. Carrier (1974) had also reported high levels of success within a 3-month period with children described as severely and profoundly retarded (American Association on Mental Deficiency Adaptive Behavior Scale, levels 4 and 5 [Nihira, Foster, Shellhaas, & Leland, 1969]). Ratings on the Adaptive Behavior Scale were obtained from the primary caretaker, who rated each child on adaptive behaviors such as the ability to brush teeth, put on clothing, and interact with others; and on nonadaptive behaviors such as violent behavior, temper tantrums, and running away.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, communication intervention has focused on the use of symbolic forms of communication (e.g., speech, pictorial, sign systems) to help the young child acquire more conventional and linguistic interaction strategies (Carrier, 1974;Oliver & Halle, 1982;Schiefelbusch & Lloyd, 1974). However, an emerging trend in the field of AAC addresses the full continuum of AAC development for all individuals with significant disabilities, regardless of age (Reichle, Beukelman, & Light, 2002).…”
Section: The Focus On Symbolic Representationmentioning
confidence: 99%